John Milton - Brown, Cedric C. author. aut Link
XVIII, 212 p.
Keywords: For the first time in an approachable, affordable volume this study treats the whole literary career of England's most distinguished protestant-republican poet and writer, considering the miscellaneous output in the light of contexts and political functions. It highlights self-presentational and persuasive characteristics, pays attention to the sense of vocation and also describes Milton's distinctive achievement in social genres. Milton's competitive humanist training is seen to accomodate uneasily to the specific demands of some public works. The book features unfamiliar texts, whilst canonical texts are set in the story of his long endeavours during a turbulent period in English history.